Advances in design and performance of dual slope solar still: A review. (15th September 2022) - Dubey, A.; Singh, S.K.; Tyagi, S.K.
Abstract: Solar distillation is a promising self-sustainable technique for achieving potable water in remote locations in an economical and eco-friendly manner. However, low productivity is the drawback of the traditional solar stills to meet the increasing demand of portable water. During the recent past, research, development, and demonstration in several directions including design, climatic and operation parameters have been enumerated to enhance the productivity of solar still. Using the paraffin wax (PCM) incorporated in the stepped design, the productivity has enhancement by 67.18%. Dual slope solar still with paraffin (PCM) and dispersed with Cu nanoparticles yields higher by 125% than the conventional design. An increase in productivity by 21.5% has been reported when nanoparticles are mixed with PCM. Active integration revealed that PVT-FPCs integrated system using CuO-based nanofluid yields ∼ 32% higher than the system operating without nanofluid. The active solar still embedded with U tube evacuated collector (ETC) yields higher by 50.97% and 55.24%, respectively, compared to the PVT-FPC, PVT-CPC integrated system. Adding PCM with still coupled with concentrator shows the increase in yield by 26%. The results reported by researchers revealed that active designs of solar still incorporated with PCMs and nanoparticles could magnify the productivity effectively and a prominent solution to meet scarcity of fresh water. The conclusions drawn from this review would facilitate the future researchers in selecting and incorporating appropriate modifications in the configuration of solar still with new phase change materials (PCMs) with nanomaterials to compete with the existing and future technologies.